2013
DOI: 10.3324/haematol.2013.096750
|View full text |Cite
|
Sign up to set email alerts
|

First description of the t(10;11)(q22;q23)/MLL-TET1 translocation in a T-cell lymphoblastic lymphoma, with subsequent lineage switch to acute myelomonocytic myeloid leukemia

Abstract: LETTERS TO THE EDITOR© F e r r a t a S t o r t i F o u n d a t i o n 2 0 1 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The TET gene family was first identified because of the involvement of TET1 as a fusion partner of MLL in acute myeloid leukemia (AML) 11 , a translocation event that has also been detected in patients with T cell lymphoma 12 and B-ALL 13 . TET1 mutations are also found at a low frequency in AML (~1%) 14 compared to T cell acute lymphoblastic leukemia (T-ALL) (~14%) 15 although mutations in B cell malignancy have not been reported.…”
mentioning
confidence: 99%
“…The TET gene family was first identified because of the involvement of TET1 as a fusion partner of MLL in acute myeloid leukemia (AML) 11 , a translocation event that has also been detected in patients with T cell lymphoma 12 and B-ALL 13 . TET1 mutations are also found at a low frequency in AML (~1%) 14 compared to T cell acute lymphoblastic leukemia (T-ALL) (~14%) 15 although mutations in B cell malignancy have not been reported.…”
mentioning
confidence: 99%
“…The fusion of TET1 and MLL has been reported in a number of AML/ALL [24, 25, 31-33]. A recent study indicates that TET1 has essential oncogenic function in the development of MLL-rearranged leukemia, which is through coordination with MLL-fusion proteins in regulating their critical co-targets including homeobox A9 (Hoxa9), myeloid ecotropic viral integration 1 (Meis1), and pre-B-cell leukemia homeobox 3 (Pbx3) genes [19, 78].…”
Section: Tet1 In Human Hematologic Malignanciesmentioning
confidence: 99%
“…In the process of demethylating DNA, TET enzymes further practice 5-hmC to generate 5-fC and 5-caC, both of which can be removed by thymine DNA glycosylase by base excision repair (BER) [22, 23, 30]. In the history of TET proteins, researches demonstrated that fusion of the N-terminal region of MLL H3K4 methyltransferase with the DSBH domain of TET1 is related with acute myeloid/lymphoid leukemias [24, 25, 31-33]. TET2 mutations correlate with many hematologic malignancies, such as myelodysplastic syndromes (MDS), myeloproliferative neoplasms (MPN), CMML, AML, secondary AML, and so on [34-42].…”
Section: Introductionmentioning
confidence: 99%
“…myeloid lineages. [8][9][10] We induced the myeloid progenitor cells by growing murine bone marrow mononuclear cells with Iscove modified Dulbecco medium containing 15% fetal bovine serum, interleukin-3, interleukin-6 and stem cell factor for 48 h. During this period, mononuclear cells were activated into myeloid progenitor cells and the number of myeloid progenitor cells was increased. The breakpoint region of the MT1 fusion between exon 9 of MLL and exon 9 of TET1 has been previously identified ( Figure 1A).…”
mentioning
confidence: 99%